Enhanced Catalytic Performance of Zn‐containing HZSM‐5 upon Selective Desilication in Ethane Dehydroaromatization Process. Issue 5 (31st January 2020) - Goodarzi, Farnoosh; Thumbayil, Rouzana Pulikkal; Enemark‐Rasmussen, Kasper; Mielby, Jerrik; Nguyen, Thoa T.M.; Beato, Pablo; Joensen, Finn; Kegnæs, Søren
Abstract: The effect of introducing mesoporosity on the catalytic stability and selectivity of Zn‐containing ZSM‐5 catalysts was investigated for direct conversion of ethane to high‐value aromatics. Voids and mesopores were created in the zeolite (Si/Al=40) by selective desilication (recrystallization) using ammonium hydroxide and cetyltrimethylammonium bromide. Zinc was incorporated in the samples by incipient wetness impregnation to achieve different concentrations of 0.5, 1 and 5 wt %. The samples were characterized by XRD, N2 physisorption, TGA, NH3 ‐TPD, ICP‐OES, FTIR, 1 H, 27 Al and 29 Si solid‐state MAS NMR. The desilicated samples were compared to their parent analogues for ethane conversion to aromatics such as benzene, toluene and xylenes (BTX). All of the desilicated samples showed an improvement in BTX yield and catalytic stability. Thus, the presence of mesoporosity increases the accessibility to the active sites and facilitates the mass transfer of aromatic compounds, which result in higher performance and catalytic stability of the desilicated ZSM‐5 samples containing zinc. Abstract : Porosity matters : We selectively desilicated zinc‐containing ZSM‐5 via a simple method. Introduction of mesoporosity suppresses coke deposition and enhances catalytic life‐time and selectivity to BTX for ethane dehydroaromatization at 550 °C, 2 barg and GHSV=0.3 h −1 .